Revisiting the Chrome Azurol S Assay for Various Metal Ions - Levican-Jaque, G; Retamal-Morales, G (Trans Tech Publications Ltd, 2017)
Siderophores play an important role in the solubilisation and mobilization of iron(III) and various metal ions. To have a useful method to test siderophores in culture supernatants for their metal binding affinity, we redesigned and optimized the liquid CAS-assay for selected metal ions. CAS-assay solutions were calibrated with desferrioxamine B in different concentrations to calculate DFOB-equivalents to get a semi-quantitative evaluation. With these assay solutions, we were able to test siderophores in culture supernatants for their ability to chelate with Fe, Al, Ga, Cu, V and As. © 2017 Trans Tech Publications, Switzerland.